Pendugaan Umur Simpan Dengan Metode Accelerated Shelf-Life Testing pada Produk Bandrek Instan dan Sirup Buah Pala (Myristica fragrans) - Didah Nur Faridah; Sedarnawati Yasni; Antin Suswantinah; Ghesi Wuri Aryani (Jurnal Ilmu Pertanian Indonesia, 2013)
Traditional beverages can be made from the spices and can be processed further as instant powder drinks such as bandrek drink. The expiration date statement on the food packaging is a mandatory according to the Food Act No.7/1996 and the Government Regulation No. 69/1999 about Food Labelling and Advertising. The aim of this research was to estimate or to predict the shelf-life of instant bandrek drink produced at Sinarsari village and nutmeg syrup at Dramaga village, Dramaga district, Bogor regency. Shelf-life estimation of the two products was done by accelerated shelf-life testing method. Instant bandrek was predicted to have shelf-life for 341 days (11 months) when stored at 80% RH, 30 °C, while the nutmeg syrup would be expired in 34-47 days when stored at 30 °C.